Interrelation of traveling ionospheric disturbances above and below the F-layer peak according to the ionosonde and the SWARM constellation data - A.D. Akchurin; G.S. Smirnov (Учёные записки Казанского университета: Серия Физико-математические науки)
One approach to determining the height structure of the mid-latitude medium-scale travelling ionospheric disturbances (MSTIDs) above the F layer peak is to involve simultaneous satellite measurements in the ground-based ionosonde measurements near Kazan. The electron concentration data obtained from the Swarm satellite constellation were the most suitable for our purposes. For accurate spatial attachment to satellite data, a strict selection of daytime satellite flythroughs data was used: their trajectory should not be located in latitude further than 100 km from the Kazan's longitude, and the spatial extent of irregularities in electron plasma density measurements should be at least more 100 km without smaller (high-frequency) irregularities. Of all the satellites in the pass es over ~ 2 years (2016–2018), we managed to select only seven such cases. For the cases found, mutual correlation functions of sequences of values of two series of the critical frequency and electron concentration were constructed. The correlation function has a bright negative peak, with a spread within 100 km, which, taking into account the typical horizontal wavelength of the MSTIDs (~ 200 km), means the antiphase behavior of electronic concentrations within the MSTID below and above the peak of the F layer of the daytime mid-latitude ionosphere.